2017
DOI: 10.1016/j.jamcollsurg.2016.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Surgical Site Infection Using Wound Photography: A Scenario-Based Study

Abstract: Background Postoperative surgical site infections (SSI) are common and costly. Most occur post-discharge, and may result in potentially preventable readmission and/or unnecessary urgent evaluation. Mobile health approaches incorporating patient-generated wound photos are being implemented in an attempt to optimize triage and management. We assessed how adding wound photos to existing data sources modifies provider decision-making. Study Design Web-based simulation survey using convenience sample of providers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 28 publications
4
42
0
Order By: Relevance
“…Another aim of this study was to examine the most important visual factors contributing to the decision of diagnosing a wound with an SSI. In a recent study, skin colour around the wound was ranked as the most important characteristic in diagnosing SSI following abdominal surgery . This is consistent with our assessments, in which those wounds with the most erythema were ultimately assessed as infected by the highest number of respondents.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Another aim of this study was to examine the most important visual factors contributing to the decision of diagnosing a wound with an SSI. In a recent study, skin colour around the wound was ranked as the most important characteristic in diagnosing SSI following abdominal surgery . This is consistent with our assessments, in which those wounds with the most erythema were ultimately assessed as infected by the highest number of respondents.…”
Section: Discussionsupporting
confidence: 89%
“…However, the response rates are unknown, and those who responded to the survey might be more used to electronic services than nonresponders. The rapidly developing field of telemedicine holds promise in increasing the efficiency of postoperative care after skin surgery, and the addition of wound photographs to clinical data has been shown to improve accuracy in diagnosing SSIs . As most dermatological procedures are performed as outpatient surgery, postoperative wound assessments through teledermatology might help in the triage and management of complications without the need for extra face‐to‐face visits.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the overall accuracy of surgeons was lower than in prior studies, presumably owing to the use of patientgenerated data and the more general population of surgeons sampled. The aforementioned study of surgical infection experts demonstrated accurate SSI detection in 67% of cases without photographs and in 76% of cases with photographs 7 (vs 57% of cases without photographs and 58% of cases with photographs in our study). A study of vascular surgeons evaluating postoperative wounds found 66% to 95% agreement between in-person and remote assessments.…”
Section: Discussionsupporting
confidence: 57%
“…In studies performed in controlled settings, the addition of wound photography alongside clinical data increases diagnostic accuracy, improves clinicians' confidence in a diagnosis, and decreases overtreatment of SSIs. 4,6,7 A limitation of prior work is that study contexts have differed from the settings in which remote assessment of wounds is currently used on an informal basis and its likely use if it were widely adopted among surgical practices. Specifically, images in prior work have typically been obtained in a uniform fashion by trained photographers.…”
mentioning
confidence: 99%
“…Assessments of wound condition will be performed by the observer and reviewed by other investigators via photographs documented in the eCRF. This will provide an objective and reliable method for the evaluation of wound infections 34. Finally, the risk that patients may experience from participating in this trial is minimal and will remain within the boundaries of routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%